A descriptive and exploratory study of factors contributing to augmented feedback duration in professional Australian football practice. Issue 3 (June 2022) - Tribolet, Rhys; Sheehan, William Bradshaw; Novak, Andrew Roman; Watsford, Mark Langley; Fransen, Job
Augmented feedback supplements or replaces task-intrinsic feedback and is common in team sports, however, no studies have reported on augmented feedback provision in professional Australian Football (AF) practice. This study investigated the effects of practice characteristics (feedback intervention frequency, practice time, practice type, season phase, practice activity form and competitive match result) on the duration of feedback provided by professional AF coaches. Two linear mixed-effects models were constructed. The first examined the collective associations between these practice characteristics and feedback durations while the second model investigated the associations between the same practice characteristics and previous match result. Results showed the feedback intervention frequency, practice time and a practice time*feedback intervention frequency interaction explained 65% of feedback duration whenever feedback was provided. Additionally, practice time, feedback intervention frequency, a practice time*match result interaction and a match result*feedback intervention frequency interaction explained 99% of feedback duration in-season. Important factors that were hypothesised to affect feedback durations in AF such as practice type, practice activity form or season phase did not contribute any explanatory power. This study provides information on how professional AF coaches provide augmented feedback in-situ and provides opportunities for skill acquisition specialists to aid coaches when delivering augmented feedback.